BronchUK: protocol for an observational cohort study and biobank in bronchiectasis. Issue 2 (19th April 2021) - De Soyza, Anthony; Mawson, Philip; Hill, Adam T.; Elborn, Stuart; Bradley, Judy M.; Haworth, Charles S.; Floto, R. Andres; Wilson, Robert; Loebinger, Michael R.; Carroll, Mary; Crichton, Megan; Chalmers, James D.; et al.
Bronchiectasis has been a largely overlooked disease area in respiratory medicine. This is reflected by a shortage of large-scale studies and lack of approved therapies, in turn leading to a variation of treatment across centres. BronchUK (Bronchiectasis Observational Cohort and Biobank UK) is a multicentre, prospective, observational cohort study working collaboratively with the European Multicentre Bronchiectasis Audit and Research Collaboration project. The inclusion criteria for patients entering the study are a clinical history consistent with bronchiectasis and computed tomography demonstrating bronchiectasis. Main exclusion criteria are 1) patients unable to provide informed consent, 2) bronchiectasis due to known cystic fibrosis or where bronchiectasis is not the main or co-dominant respiratory disease, 3) age <18 years, and 4) prior lung transplantation for bronchiectasis. The study is aligned to standard UK National Health Service (NHS) practice with an aim to recruit a minimum of 1500 patients from across at least nine secondary care centres. Patient data collected at baseline includes demographics, aetiology testing, comorbidities, lung function, radiology, treatments, microbiology and quality of life. Patients are followed up annually for a maximum of 5 years and, where able, blood and/or sputa samples are collected and stored in a central biobank. BronchUK aims to collect robust longitudinal data that can be used for analysis into current NHS practice and patient outcomes, and to become an integral resource to better inform future interventional studies in bronchiectasis. BronchUK is a multicentre, observational cohort study and biobank collecting longitudinal patient data to be used for analysis into current NHS practice and patient outcomes, and to better inform the design of future interventional studies https://bit.ly/3svngZc